XX/XY System of Sex Determination in the Geophilomorph Centipede Strigamia maritima - Green, Jack E; Dalíková, Martina; Sahara, Ken; Marec, František; Akam, Michael (PloS one, 2016)
We show that the geophilomorph centipede Strigamia maritima possesses an XX/XY system of sex chromosomes, with males being the heterogametic sex. This is, to our knowledge, the first report of sex chromosomes in any geophilomorph centipede. Using the recently assembled Strigamia genome sequence, we identified a set of scaffolds differentially represented in male and female DNA sequence. Using quantitative real-time PCR, we confirmed that three candidate X chromosome-derived scaffolds are present at approximately twice the copy number in females as in males. Furthermore, we confirmed that six candidate Y chromosome-derived scaffolds contain male-specific sequences. Finally, using this molecular information, we designed an X chromosome-specific DNA probe and performed fluorescent in situ hybridization against mitotic and meiotic chromosome spreads to identify the Strigamia XY sex-chromosome pair cytologically. We found that the X and Y chromosomes are recognizably different in size during the early pachytene stage of meiosis, and exhibit incomplete and delayed pairing.
Keywords: Animals; chromozom X; Y Chromosome; srovnávací genomová hybridizace; Female; ženské pohlaví; členovci; procesy určující pohlaví; Arthropods; Male; X Chromosome; Comparative Genomic Hybridization; hybridizace in situ fluorescenční; Sex Determination Processes; zvířata; mužské pohlaví; In Situ Hybridization, Fluorescence; kvantitativní polymerázová řetězová reakce; chromozom Y; Real-Time Polymerase Chain Reaction